The Use of Canva Aplication as An Effective and Innovative Learning Media - Harianto, Dedi; Ahmad, Ahmad; Utami, Sri (DIDAKTIKA, 2025)
Learning media, as a medium for delivering content across various educational levels, comes in various forms that can be selected according to the specific and effective learning material needs. The use of the technology Canva as an example of an effective and innovative learning medium, particularly popular today, is visual-based media. Canva is an application that provides tools for creating engaging visual learning media, which can enhance the interest of its users, making it an effective and efficient learning tool. This research aims to explore the use of Canva in the creation of learning media. Based on an analysis of previous studies, Canva has proven capable of producing engaging and effective visual learning media designs. The method employed in this research is an exploratory approach, with qualitative methods as relevant scientific literature. Therefore, utilizing the Canva application as a digital learning platform is very appropriate.Keywords: Canva Application, Effective and Innovative, Learning Media.